2017
DOI: 10.1155/2017/8163762
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Malaria and ABO Blood Types in East China

Abstract: Objectives This study aims at investigating the relationship between malaria and blood group types in east China. Methods Between 1 January 2011 and 31 March 2017, 99 malaria patients were enrolled for the study. Laboratory tests were conducted on their infection status and blood types. Clinical data of the participants were retrieved for analysis. Results There was no mortality during the period of study. Overall, 90 (90.91%) of the patients were positive for Plasmodium falciparum, 8 (8.08%) were infected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
1
1
2
Order By: Relevance
“…There was no significant correlation between malaria and blood group. This agrees with the findings of [36]. However, there was a significant correlation between malaria parasitemia and age as children were observed to be more prone to malaria compared to adults and this is similar to the findings of Schwartz et al [37].…”
Section: Discussionsupporting
confidence: 92%
“…There was no significant correlation between malaria and blood group. This agrees with the findings of [36]. However, there was a significant correlation between malaria parasitemia and age as children were observed to be more prone to malaria compared to adults and this is similar to the findings of Schwartz et al [37].…”
Section: Discussionsupporting
confidence: 92%
“…This result is in agreement with the findings done in Sri Lanka, 32 Sudan, 33 and across different corners of Ethiopia. 19,22,34 However, this study was contrary to the findings conducted in China, 35 Burkina Faso, 36 Ghana 37 and Nigeria 38 which reported malaria infection was generally higher in O blood groups than other blood groups. This discrepancy in results could due to…”
Section: Discussioncontrasting
confidence: 82%
“…Various studies have been performed on the effect of blood groups on the incidence and severity of different infectious diseases. A study examining the link between malaria and blood types in China found that blood type O (38.38%) had the highest prevalence among patients with malaria, but no statistically significant relationship was found between blood groups and malaria prevalence, 30 whereas in another study on the issue, the most common blood type was B. 31 In an epidemiological study of 34 hospital staff who became infected with the severe acute respiratory syndrome (SARS) after being exposed to a single patient, most of the infected people (23/34) had non-O blood types (A, B, and AB), and group O individuals are more resistant to SARS-CoV due to ABO antibodies.…”
Section: Discussionmentioning
confidence: 99%